The Influence of Socialization on Students' Knowledge Levels About Antibiotic Resistance in Selong District, East Lombok: Pengaruh Edukasi Terhadap Tingkat Pengetahuan Siswa Tentang Resistensi Antibiotik di Kecamatan Selong, Lombok Timur - Risma Fatmayanti, Baiq; Ramadhan, Leny; Rafsanjani, Arief; Marlita, Jeli; Azim, Muhlisun; Febriani, Yuyun (Universitas Haji Sumatera Utara, 2025)
Antibiotics are drugs used to treat bacterial infections. Irrational use of antibiotics without a doctor's prescription causes antibiotic resistance. West Nusa Tenggara province is ranked sixth with the largest number of antibiotic consumption without a doctor's prescription so the incidence of antibiotic resistance increases. This community service aims to provide antibiotic resistance education to high school students in Selong District. The community service method was carried out at SMAN 1 Selong and SMAN 2 Selong which started with pretest, socialization, and posttest activities to measure students' knowledge of antibiotic resistance before and after socialization. The significance test of changes in students' knowledge levels before and after socialization was conducted using a paired sample t-test. The socialization participants from SMAN 1 Selong and SMAN 2 Selong consisted of 141 high school students in grade XI with an average age of 16. The pretest and posttest data analysis showed that students' knowledge levels regarding antibiotic resistance increased from 41% to 59% at SMAN 1 Selong and 42% to 58% at SMAN 2 Selong after socialization. The average value of students' knowledge about antibiotic resistance increased from 10.04 points to 14.73 points for SMAN 1 Selong and 10.33 points to 14.16 points for SMAN 2 Selong after the socialization was given from a total of 17 maximum points that could be obtained. The results of data analysis using paired sample t-test showed a significant difference (p<0.05) in the average level of student knowledge before and after the socialization activity was carried out. Thus, the antibiotic resistance socialization activity has successfully increased student knowledge in Selong District, especially at SMAN 1 Selong and SMAN 2 Selong effectively.